KEBIJAKAN DAN PERAN PEMERINTAH DAERAH DALAM MENDUKUNG KEHADIRAN TREN E-COMMERCE DALAM MASYARAKAT TORAJA - Reti Sriwahyuni Pradoso (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2023)
The development of e-commerce has become a significant phenomenon in the world of global trade. In Indonesia, the growth of e-commerce is very rapid and has the potential to have a positive impact, especially for Micro, Small and Medium Enterprises (MSMEs) in the Tana Toraja area. However, there are still challenges in adopting e-commerce, such as a better understanding of the use of e-commerce platforms and the role and policies of governments in supporting this trend. This study aims to examine the role and policies of local governments in supporting the development of e-commerce in the Tana Toraja community. This study is urgent because e-commerce has the potential to increase sales of Tana Toraja MSMEs and contribute to economic growth and community welfare. This research uses qualitative research methods by collecting data through a review of related literature. The data was analyzed to understand the role and policies of local governments in supporting e-commerce in Tana Toraja. Qualitative methods help in gaining an in-depth understanding of complex issues related to e-commerce. The results showed that the local government of Tana Toraja plays an important role in supporting the development of e-commerce, especially in terms of funding, taxation, logistics, tourism, and education. Through initiatives and cooperation with various parties, local governments contribute to facilitating e-commerce as a means for economic growth and empowerment of MSMEs. Thus, understanding and developing the role and policies of local governments in supporting e-commerce is very important in facing changing global business trends.